Hydroethanolic Cyperus rotundus L. extract exhibits anti-obesity property and increases lifespan expectancy in Drosophila melanogaster fed a high-fat diet - Nattapong Wongchum; Ananya Dechakhamphu; Panatda Panya; Somchai Pinlaor; Sitthisak Pinmongkhonkul; Alongklod Tanomtong (Shahrekord University of Medical Sciences, 2022)
Introduction: Cyperus rotundus L. is suspected of having anti-obesity properties. The purpose of this study was to determine the anti-obesity property of hydroethanolic C. rotundus extract (HECE) using Drosophila as a model organism. Methods: In vitro inhibition of lipase activity by C. rotundus extract was investigated. The effects of C. rotundus extract on obesity-related characteristics, including body weight, triglyceride content, and lifespan extension were evaluated in Drosophila fed a high-fat diet (HFD). The effect of the extract on the reduction of oxidative stress associated with obesity was assessed in vivo using antioxidant assays in Drosophila. Results: HECE inhibited lipase activity in vitro with an IC50 of 128.24 ± 3.65 μg/mL. In vivo lipase inhibition experiments demonstrated that feeding Drosophila 10 mg/mL HECE or 2 μM orlistat lowered lipase activity by 21.51 (P < 0.05) and 42.86% (P < 0.01) and triglyceride levels by 20.67 (P < 0.05) and 28.39% (P < 0.01), respectively, compared to those of the untreated group. After 10 mg/mL HECE or 2 μM orlistat supplementation, an increase in the mean survival rate (10.54 (P < 0.05) and 13.90% (P < 0.01), respectively) and climbing ability (25.03 (P < 0.01) and 28.44% (P < 0.01), respectively) was observed compared to those of flies fed a HFD. The paraquat and H2O2 challenge tests revealed that flies fed HECE in a mixed HFD showed increased survival on flies fed a HFD. Conclusion: This study demonstrates the beneficial effects of dietary HECE supplementation on suppressing pancreatic lipase activity and lowering triglyceride levels and oxidative stress, leading to increased lifespan in Drosophila fed a HFD.